효소 처리 밀 배아 추출물의 화학적 특성 변화 - 이재강(Jae-Kang Lee); 장다빈(Davin Jang); 강동우(Dongwoo Kang); 이정훈(Jeonghoon Lee); 금혜임(Hyeim Kum); 최용현(Yonghyoun Choi); 강희(Hee Kang); 최용석(Yong-Seok Choi); 김대옥(Dae-Ok Kim) (Han'guk Sikp'um Kwahakhoe Chi = Korean Journal of Food Science and Technology, 2019)
Wheat germ, which is rich in nutrients and phytochemicals, is a by-product during the milling process of wheat kernel. In this study, we aimed to increase the amount of bioactive 2,6-dimethoxy-1,4-benzoquinone (2,6-DMBQ) in wheat germ using the cell-wall-degrading enzyme cellulase (Celluclast 1.5L). The amounts of organic acids, free sugars, and 2,6-DMBQ in wheat germ treated with Celluclast 1.5L were evaluated at various reaction times and temperatures. The results of reversed-phase high-performance liquid chromatography of Celluclast 1.5L-treated wheat germ revealed 2,6-DMBQ, four organic acids (tartaric, acetic, lactic, and succinic acids), and three free sugars (sucrose, fructose, and glucose). As reaction time and temperature of the mixture of wheat germ and Celluclast 1.5L increased, the contents of four organic acids, glucose, fructose, and 2,6-DMBQ increased, but that of sucrose decreased. Taken together, these results suggest that Celluclast 1.5L-treated wheat germ containing increased amounts of 2,6-DMBQ serves as a source of functional ingredients in food industry.